Effect of reduced rainfall on N2O emissions in agricultural rotations with cover crops - Restovich, Silvina Beatriz; Posse Beaulieu, Gabriela; Portela, Silvina Isabel; Frasier, Ileana; Beribe, Maria Jose; Rodriguez, Santiago; Dalpiaz, Maria Jimena; Torti, Maria Juliana; Garcia, Leticia Soledad (AARHUS University, 2024)
Poster